An application of the decomposition method for the two-dimensional KdV-Burgers equation - Kaya, D (Pergamon-Elsevier Science Ltd, 2004)
A relatively new decomposition method is presented to find the explicit and numerical solutions of the two-dimensional Korteweg-de Vries Burgers' equation (tdKdVB for short) for the initial conditions. Some numerical results are also given for this equation by using the decomposition method. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: the decomposition method; Korteweg-de Vries equation; Burgers' equation; two-dimensional Korteweg-de Vries Burgers' equation; soliton solution